Molecular Pathogenesis and Management of Atopic Dermatitis: A Comprehensive Review - Aryasta, Ida Bagus Putra Bayu; Rahman, Hadian (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Atopic dermatitis (AD) is a chronic inflammatory skin disease with rising global prevalence and substantial health and psychosocial burden. This review aims to summarize recent advances in molecular pathogenesis and management of AD. Literature was searched in PubMed, ScienceDirect, Google Scholar, and accredited national journals, focusing on the past ten years. Inclusion criteria were full-text articles in English or Indonesian addressing epidemiology, pathogenesis, clinical features, and management. Irrelevant or incomplete studies were excluded. Selected articles were screened, classified by theme, and analyzed narratively following PRISMA guidelines. Findings show that AD prevalence continues to increase worldwide, with major impacts from chronic pruritus, recurrent flares, and psychosocial distress. Key mechanisms include genetic predisposition, especially filaggrin mutations, and immune dysregulation involving Th2, Th17, and Th22 pathways. Current treatments range from topical therapies to biologics and JAK inhibitors, emphasizing individualized care. In conclusion, AD is a lifelong multifactorial disease requiring comprehensive management. Advances in pathophysiology have expanded therapeutic options, with biologics and JAK inhibitors showing strong efficacy. Globally, priorities include precision medicine, early intervention, and wider access to novel therapies. In Indonesia, urgent needs are early detection in primary care, integration of AD management into national health programs, and ensuring affordable treatment access.